(untitled) (Fiep Bulletin - online, 2011)
Objectives: Indentified and compare the anthropometrical growth and motor development level of children with leukemia in the beginning of the chemotherapy treatment with children without leukemia. Method: This is a transversal cut research with delineated comparison. For motor development evaluation purpose, the Rosa Neto (2002) Scale of Motor Development Test has been applied, which comprehends a battery test involving in the components specified tasks by age: fine Motricity, global Motricity, balance, body scheme, space organization and temporal organization. The sample was separated in two groups: experimental and control, the experimental group has comprehended 12 children, whom ages have ranged from 02 to 05 years old, from both sexes, with cancer disease, and the control group composed by 10 children of the same age bracket, of both sexes students, without cancer of the Cremação Infantile Education Municipal School of Belém-BRAZIL. Result: The groups have obtained similar results for the investigated variables means. It has been verified that the children have been shown motor classification among the standards "medium normal", "high normal" and "much low". Conclusion: The study has concluded that the chronological and motor age of the children, compared between the groups, are normal according to parameters of normality as motor development and anthropometry. It hasn’t been observed statistically differences, which have been confirmed between the investigated variables means. It’s been suggested longitudinal researches that can visualize if the utilization of chemotherapy may alter the anthropometrical components or the motor development of children with cancer.